Washington Manual(R) Pulmonary Medicine Subspecialty Consult, The, 1st Edition - Shifren, Adrian (Lippincott Williams & Wilkins, 2006)
This is the first printing of The Washington ManualÃ‚Â® Pulmonary Medicine Subspecialty Consult. The goal of this book is to provide the medical student, resident, and pulmonary fellow on a pulmonary medicine service with a handbook that will be helpful in the evaluation of patients with pulmonary disease. It is also hoped that it will serve as a quick reference for internists and nonpulmonary physicians in practice. As such, it is not intended as a complete reference of pulmonary medicine, but rather as a focused source of information that will assist in the process of history taking, physical examination, and testing as it pertains to the patient concerned. Our knowledge of pulmonary medicine has grown exponentially over the last 40 years and is continually expanding. Reflecting this are the increasing complexity and bulk of the current general pulmonary texts. To simplify matters and effectively address our target audience, each chapter has been written with the input of either a medical resident or a pulmonary fellow. The chapters have been further evaluated by attending physicians with expertise in the relevant field to ensure accurate information. At the end of each chapter is a list of references that were chosen for their relevant content. These references will serve as an excellent starting point for further reading. The chapters have been organized in a simple fashion and, where possible, deal with a single pulmonary entity of the type often faced by the consulting pulmonary team (e.g., solitary pulmonary nodule). When the topic is more complex (e.g., interstitial lung disease), the approach is more generalized. A book like this is always a collective effort, with many of the contributors working in the background. With that in mind, I would like to thank Kate Sallwasser for all her help, and Lauren Aquino, without whom this book would not have reached completion. Finally, it is my hope that this book enriches both the reader's medical knowledge in general and appreciation of pulmonary medicine in particular. Ideally, the small contribution made to each physician or physician-in-training by this book will result in the improved care of patients.